Mirounga leonina - Jackson, Stephen M.; Jansen, Justin J. F. J.; Baglione, Gabrielle; Callou, Cécile (Zenodo, 2021)
Phoca proboscidea Péron in Péron & Freycinet, 1816 Phoca proboscidea Péron in Péron & Freycinet, 1816. pl. 32 from Lesueur & Petit 1807. COMMON NAME. — Elephant Seal. CURRENT NAME. — Mirounga leonina (Linnaeus, 1758). See Jackson & Groves (2015: 302) and Stewart (2014: 171). COLLECTOR/S. — No data. Observed by Péron (Girard 1856: 98). COLLECTION LOCALITY. — King Island, Tasmania. King Island according toPéron (1804a). COLLECTION DATE. — Between 8 and 27 December 1802. SPECIMEN NUMBER/S. — No data. ILLUSTRATIONS. — Illustrated by Charles-Alexandre Lesueur – Muséum d’Histoire naturelle du Havre, Inv. no. 80001 (Fig. 172; three live animals) (Fornasiero et al. 2016: 131), Inv 80007 (Fig. 173; three live animals; engraving from Jacques Milbert from a drawing by Lesueur) (Fornasiero et al. 2016: 131), Inv. no. 80002 and 80003 (Figs 174; 175; sketch of one live animal) (Fornasiero et al. 2016: 131), Inv. no. 80004, 80005 and 80006 (Figs 176-178; two live animals) (Fornasiero et al. 2016: 100) Published as part of Jackson, Stephen M., Jansen, Justin J. F. J., Baglione, Gabrielle & Callou, Cécile, 2021, Mammals collected and illustrated by the Baudin Expedition to Australia and Timor (1800 - 1804): A review of the current taxonomy of specimens in the Muséum national d'Histoire naturelle de Paris and the illustrations in the Muséum d'Histoire naturelle du Havre, pp. 387-548 in Zoosystema 43 (21) on pages 436-437, DOI:10.5252/zoosystema2021v43a21, http://zenodo.org/record/5142972